PERAN BIAYA PUBLIK, TATA KELOLA PEMERINTAH DAN SISTEM ANGGARAN PEMERINTAH TERHADAP KEPUASAN MASYARAKAT DI JABODETABEK - Hurian Kamela; Dede Puspa Pujia; Adibah Yahya; Kiko Armenita Julito (Universitas Kristen Krida Wacana, 2026)
This study analyses the influence of public expenditure, government governance, and the government budgeting system on community satisfaction in the Jabodetabek region. Community satisfaction is an important indicator of public sector performance, particularly in relation to accountability and transparency in public financial management. The research employs a quantitative, survey-based approach. The population consists of residents in the Jabodetabek area, with 164 respondents selected through purposive sampling. Data were collected using structured questionnaires and analysed using descriptive statistics and multiple linear regression analysis to test the proposed hypotheses. The results show that public expenditure has a positive and significant effect on community satisfaction, indicating that effective and efficient use of public funds improves public perceptions of government performance. Government governance also has a positive, significant influence on community satisfaction, underscoring the importance of transparency, accountability, and public participation in governance processes. In addition, the government budgeting system significantly affects community satisfaction, reflecting the role of proper budget planning, allocation, and implementation in meeting public needs. This study provides empirical evidence on the integrated roles of public expenditure, governance, and budgeting systems in shaping community satisfaction, offering policymakers valuable insights to improve public financial management and the quality of public services.